Rancang Bangun Aplikasi Mobile Buku Nyanyian Gereja Berdasarkan User Centered Design (UCD) - Tadonny Vani; Arnoldus Y.F. Danar Yudhistira; Billy Re Satria (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
In the era of industrial revolution 4.0, people prefer to use digital services that are instantaneous and practical, including hymns of praise or spiritual songs for worship activities in the congregation of GKE Nanga Bulik. This study aims to produce an android-based mobile application that can be used to support worship activities, especially in the service of hymns or spiritual songs in the Congregation of GKE Nanga Bulik. This research was conducted in several stages, named the Data Collection Stage, the System Design Stage and the Report Writing Stage. The system design stage was developed based on the User Centered Design (UCD) method. The result showed that a mobile application was in accordance with user needs and was presented as a new innovation in the Congregation of GKE Nanga Bulik.